Accumulative traction-hoisting construction technology of a semi-rigid steel batten cable dome. (June 2021) - Ding, Ming-min; Luo, Bin; Guan, Dong-zhi; Wei, Yang; Ding, Shu-yao; Huang, Li-fan
Abstract: A new structure called a steel-batten cable dome (SBCD) is proposed in this study. By replacing flexible ridge cables to semi-rigid steel battens, this structure is provided with the characteristics of good integrity and large local stiffness to support heavy rigid roofing systems. In addition to avoid installing large amount of temporary stent, the accumulative traction-hoisting construction technology (ATHC) was present, with the feathers of few brackets, small lifting force, and high efficiency of tensioning. Moreover, the modified NDFEM form-finding method is introduced to simulate the construction process of ATHC. The results show that the SBCD model and the conventional cable dome (CCD) model both experienced the traction-hoisting stage, the adjustment stage, and the rigid stage to build sufficient stiffness to withstand external load, with their overall shapes changing from "ω" to "m", and finally reach their designed states. Total stresses of the steel battens are within 85 MPa before final forming and 250 MPa after construction, which ensures the stable state for the steel batten grid and the elastic state of the entire structure. Furthermore, ATHC can be applied for both SBCDs and CCDs, while a SBCD could be simplified to a similar CCD to optimize the calculation efficiency.